Automated clothesline for home application / Nur Hasmidah Hassim - Hassim, Nur Hasmidah (2024)
The automated clothesline system is a technologically advanced solution designed to address the inconvenience of unexpected rain while drying clothes outdoors. It consists of various sensors, a microcontroller, a motor, and output elements, including a light- dependent resistor, water sensor, and ultrasonic sensor. The microcontrollers, Arduino Uno R3 and ESP01, facilitate intelligent control of the system, processing information from the sensors and orchestrating subsequent actions. The control mechanism uses a stepper motor, a Light Emitting Diode (LED), and a buzzer as output components. The project underwent rigorous development and testing, with circuits meticulously constructed and evaluated for optimal functionality. The microcontroller's programming was critical for precise motor control and seamless integration of all components. A miniature model was created before the final prototype, providing a scaled representation of the entire system. The successful implementation of this project showcases its practicality and potential to enhance the efficiency of traditional clothes drying methods, especially in unpredictable weather conditions.